2021
DOI: 10.1111/stan.12252
|View full text |Cite
|
Sign up to set email alerts
|

Goodness‐of‐fit tests for Poisson count time series based on the Stein–Chen identity

Abstract: To test the null hypothesis of a Poisson marginal distribution, test statistics based on the Stein-Chen identity are proposed. For a wide class of Poisson count time series, the asymptotic distribution of different types of Stein-Chen statistics is derived, also if multiple statistics are jointly applied. The performance of the tests is analyzed with simulations, as well as the question which Stein-Chen functions should be used for which alternative. Illustrative data examples are presented, and possible exten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 32 publications
4
11
0
Order By: Relevance
“…The SC bound does not seem to be commonly used; however, related references are available [5][6][7][8][9][10]. For example, Ref.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The SC bound does not seem to be commonly used; however, related references are available [5][6][7][8][9][10]. For example, Ref.…”
Section: Discussionmentioning
confidence: 99%
“…[7] applies the SC method to calculate coincidence probabilities. References [8,9] apply the SC method in different time series contexts than considered here. To simplify the calculation of bivariate Poisson moments, Ref.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Aleksandrov et al. (2022), it is suggested to use the Poisson identity (1) with an appropriate choice of f for developing a moment‐based GoF‐test for the Poisson distribution (note that different types of GoF‐test, but also being related to a Stein characterization, are derived by Yang et al. (2018) and Betsch et al.…”
Section: Introductionmentioning
confidence: 99%
“…In their simulation experiments, Aleksandrov et al. (2022) observed that the empirical power of the tests for different alternatives strongly depends on the choice of f . For example, for an NB‐alternative, the choice f(x)=false|x1false|a$f(x)=|x-1|^a$ with a close to 1 leads to a good power, whereas ffalse(xfalse)=expfalse(xfalse)$f(x)=\exp (-x)$ appears to be a good choice for a zero‐inflated Poisson (ZIP) alternative.…”
Section: Introductionmentioning
confidence: 99%